Transport analysis of an air gap membrane distillation (AGMD) process - Hawlader, Mohammad Nurul Alam; Bahar, Rubina; Kim, Choon Ng; Loh , Jian Wei Stanley (Desalination Publications, 2012)
Membrane distillation (MD) desalination is an emerging technology for fresh water production. This process incorporates phase change and transport of vapour through a hydrophobic membrane caused by vapour pressure across the membrane. The results from experimental studies and the one-dimensional transport analyses of the heat and mass transfer processes on an air gap MD (AGMD) unit are presented in this paper. The effects of different operating variables including feed and coolant temperatures, air gap, membrane support mesh size, feed concentration and feed and coolant fl ow rates were investigated. Mass transport through membrane, membrane support, air gap and condensation on the coolant plate has been analysed and expression for global mass transfer coeffi cient has been derived. The maximum distillate fl ux achieved was 5.11 kg m−2 h at a feed temperature of 60°C, coolant temperature of 10°C and an air gap of 2.5 mm. Feed temperature and air gap width were found to have signifi cant infl uence on the performance of the membranes.